Suffering Technology (Part 2) - Tham, L.C., Joseph (Studia Bioethica, 2014)
We can better appreciate many current bioethical dilemmas in terms of human suffering and its alleviation by means of modern technology. In part one of the article, we see how suffering is a ubiquitous experience, and human responses are found in two categories—religious explanations that find answers in a transcendent kingdom and immanent solutions to banish pain by technical means. As societies became more secular, technological solutions prevailed. Certainly, modern advances have brought us greater comforts, curing many diseases and prolonging lives. Nonetheless, these technologies are not without ambiguities, and can be causes of anguish. The debates surrounding stem cells and end of life issues are examples of these ironies, where miracle cures or lifesaving machines can diminish our humanity. In part two of the article, a historical and philosophical analysis of technology offers a deeper understanding of our present predicament. Accordingly, this paper examines the thoughts of Plato, Aristotle, Bacon, Hobbes, Gehlen, Hans Jonas, Heidegger and Romano Guardini on the subject. However, philosophy cannot fully resolve the enigma of suffering. This brings us to examine once more the contribution of theology, especially by focusing on certain insights on the virtue of hope in the encyclical Spe Salvi.